Surprise, Surprise : What Drives the Rand / U.S. Dollar Exchange Rate Volatility? - Mavee, Nasha; Perrelli, Roberto; Schimmelpfennig, Axel. (Washington, D.C. : International Monetary Fund, 2016)
This paper investigates possible drivers of volatility in the South African rand since the onset of the global financial crisis. We assess the role played by local and international economic surprises, commodity price volatility, global market risk perceptions, and local political uncertainty. As a measure of rand volatility, the study uses a market-based implied volatility indicator for the rand / U.S. dollar exchange rate. Economic surprises-the difference between market expectations and data prints-are captured by Citi's Economic Surprise Index which is available for South Africa and its main economic partners. The results suggest that rand volatility is mainly driven by commodity price volatility, and global market volatility, as well as domestic political uncertainty. In addition, economic surprises originating in the United States matter, but not those originating from South Africa, Europe, or China.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet